PENGARUH KOMPONEN-KOMPONEN PEMBENTUK PAJAK TANGGUHAN TERHADAP MANAJEMEN LABA PERUSAHAAN MANUFAKTUR DI BEI - Tandio, Lydiawati; Hariyanto, Simon; Irawan, Ronny (Widya Mandala Surabaya Catholic University, 2014)
Earnings management activities which were detected in book-tax differences can be done by raising the net deferred tax liabilities that result in the ascension of deferred tax expenses. This study is aimed at identifying and examines the effect of their components net deferred tax liabilities and against the indications of earnings management. The components of deferred tax being analyzed are accrual and provision for income and expenses, compensation, depreciation, valuation of assets and other miscellaneous items. The object of the research is the manufacturing companies listed on the Stock Exchange in 2009-2012 which has been selected by purposive sampling technique. This research was tested using logistic regression. The results showed that the change in net deferred tax liabilities along with its components such as accrual and provision for income and expenses, compensation, depreciation, valuation of assets and other miscellaneous items had no significant effect on earnings management to increase profit accounting. Operational cash flow as control variable had no significant effect on earning management to increase profit accounting.